2021
DOI: 10.1101/2021.05.31.445667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing the host antiviral protein ZAP-S as an inhibitor of SARS-CoV-2 programmed ribosomal frameshifting

Abstract: Programmed ribosomal frameshifting (PRF) is a fundamental gene expression event in many viruses including SARS-CoV-2, which allows production of essential structural and replicative enzymes from an alternative reading frame. Despite the importance of PRF for the viral life cycle, it is still largely unknown how and to what extent cellular factors alter mechanical properties of frameshifting RNA molecules and thereby impact virulence. This prompted us to comprehensively dissect the interplay between the host pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(114 reference statements)
1
3
0
Order By: Relevance
“…Thus, while essential for RNA-binding and CpG specificity, the RBD likely has no intrinsic antiviral activity alone at physiological expression levels. A recent preprint has suggested that ZAP-S can inhibit SARS CoV-2 by negatively regulating the -1 frameshift between Orf1a and Orf1b [48]. Consistent with this, we do see a small reduction in N expression in infected cells expressing ZAP-S alone, but it is insufficient to significantly impact viral production in the supernatant.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, while essential for RNA-binding and CpG specificity, the RBD likely has no intrinsic antiviral activity alone at physiological expression levels. A recent preprint has suggested that ZAP-S can inhibit SARS CoV-2 by negatively regulating the -1 frameshift between Orf1a and Orf1b [48]. Consistent with this, we do see a small reduction in N expression in infected cells expressing ZAP-S alone, but it is insufficient to significantly impact viral production in the supernatant.…”
Section: Discussionsupporting
confidence: 88%
“…In epithelial cell lines, ATXN2L regulates stress granules and processing bodies (Kaehler et al, 2012). ZC3HAV1 was shown to destabilize IFNB and IFNL3 mRNAs in hepatocytes, and human cytomegalovirus RNA in fibroblasts, and it inhibits programmed ribosomal frameshifting of the SARS-CoV-2 virus (Schwerk et al, 2019;Gonzalez-Perez et al, 2021;Zimmer et al, 2021). The mechanisms that ATXN2L and ZC3HAV1 employ in T cells to supress cytokine production, however, await further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Another important antiviral mechanism is the inhibition of protein translation from viral mRNAs. The binding of PARP13 to viral RNAs can reduce their association with ribosomes, reducing their translation [45,46], and recent evidence suggests that specific ribosome frameshifting events, such as the ORF1a/b slippage event in SARS-CoV-2 can be regulated by PARP13 binding as well [47]. Strong inhibition of protein synthesis was also observed in cells overexpressing PARP7, PARP10 or PARP12L (the long isoform of PARP12) from virally encoded constructs, although a clear mechanistic understanding of this effect is currently lacking [28,29,48].…”
Section: Adp-ribosylation and Ifn-induced Effector Functionsmentioning
confidence: 99%